The use of biologically active components from diverse sources in developing new local hemostatic agents - Kletnieks Ugis; Sokolovsky, S.; Gladyshev, V.; Abramov, S.; Гладишев, Віталій Валентинович (My University, 2023)
Recent advances in biotechnology and nanotechnology have led to the development of novel hemostatic agents with improved properties. A hemostatic powder named "PLANTOR" has been developed using biologically active components and has been suggested as a supplementary method for revitalization and local coagulation during emergency medical care to stop external bleeding.
Keywords: тези доповідей